Symmetrical and Asymmetrical of TAM: Consumer Emotional Value and Service Innovation on Consumer Purchase Decisions - Juniansyah, Dedi; Putra, Aditya Halim Perdana Kusuma; Syahnur, Haerdiansyah; Hasan, Sabri; Nujum, Syamsu (Manunggal Halim Jaya, 2022)
This article presents the results of the mapping carried out taken from various sources, with a total of 34 papers used as mapping materials. Based on the existing theory, TAM consists of several factors, namely risk factors, usability, and added value. The community can accept the stronger these three factors, the more robust technology. These factors can lead to an acceptance of feelings of emotional value or commonly refer to as perceived emotional value. A person can receive emotional value after using the technology, and an emotional value can occur because of innovation. These two things can make a decision someone will use the technology. This study aims to determine the symmetrical and asymmetrical relationship between TAM and Emotional Value, Service Innovators, and also Consumer Purchase Decisions.